2014
DOI: 10.1021/mp5003009
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Releasing d-α-Tocopheryl Polyethylene Glycol Succinate for Enhancing Antitumor Activity of Doxorubicin

Abstract: Nitric oxide (NO) has attracted much attention for its antitumor activity and synergistic effects when codelivered with anticancer agents. However, due to its chemical instability and short half-life, delivering gaseous NO directly to tumors is still challenging. Herein, we synthesized a NO releasing polymer, nitrate functionalized d-α-tocopheryl polyethylene glycol succinate (TNO3). TNO3 was able to self-assemble into stable micelles in physiological conditions, accumulate in tumors, and release ∼90% of NO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 55 publications
1
65
0
2
Order By: Relevance
“…The potential of NO delivery systems in overcoming MDR was first demonstrated in vivo by the Si and Zhang groups (Figure 1) [66]. They developed NO-releasing micelles (TNO 3 ) by modifying the hydrophilic polyethylene glycol (PEG) end group of FDA-approved d -α-tocopheryl polyethylene glycol succinate (TPGS) with NO-releasing nitrate (-ONO 2 ).…”
Section: Progress Of Combined No and Drug Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential of NO delivery systems in overcoming MDR was first demonstrated in vivo by the Si and Zhang groups (Figure 1) [66]. They developed NO-releasing micelles (TNO 3 ) by modifying the hydrophilic polyethylene glycol (PEG) end group of FDA-approved d -α-tocopheryl polyethylene glycol succinate (TPGS) with NO-releasing nitrate (-ONO 2 ).…”
Section: Progress Of Combined No and Drug Delivery Systemsmentioning
confidence: 99%
“…Third, it is largely unknown whether the combined NO and drug delivery systems can exert synergistic effect in anticancer therapy. Although all strategies discussed above showed higher cytotoxicity than NO or drug treatment alone, only one study demonstrated that co-treatment had a CDI of less than 0.7 [66]. Fourth, proper range of NO concentrations for overcoming MDR should be demonstrated.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…It was thus demonstrated that the BBB might be overcome by micelles with a size of $550 nm and cause non-selective accumulation of DTX in brain. The TPGS micelles were able to inhibit p-glycoprotein (p-gp)-based drug efflux in BBB that leads to enhancement in brain DTX concentrations (Zhao et al, 2013a;Song et al, 2014). Further, the control DTX showed the lowest concentration in the brain as a result of the resistance from the BBB as well as the enhanced elimination rate from the body.…”
Section: Formulation Codementioning
confidence: 99%
“…After treatment for 24, 48, and 72 hours, respectively, the relative cell viability was assessed by an MTT assay as described in our previous work. 31 IC 50 (concentration resulting in 50% inhibition of cell growth) value was determined by SPSS software (version 19.0). The experiment was repeated thrice.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%